2015
DOI: 10.1177/230949901502300209
|View full text |Cite
|
Sign up to set email alerts
|

Screw Length in Volar Locking Plate Fixation for Distal Radial Fractures

Abstract: Purpose. To develop a reference for the distal screw length in volar locking plate fixation for distal radial fractures in an East Asian population. Methods. 12 pairs of forearm specimens from 11 male and one female East Asian cadavers were scanned using computed tomography. On sagittal images of the distal radius, the mean cortex-to-cortex distance of 8 quadrants was measured as a reference for the distal screw length. In addition, intra-operative 3-dimensional fluoroscopy of 10 male and 10 female patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
3
7
0
Order By: Relevance
“…The measurements of the epiphyseal screws lengths in the entire cohort are in accordance with a previous study by Yuen et al. (2015) on 12 East Asian cadaveric specimens.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The measurements of the epiphyseal screws lengths in the entire cohort are in accordance with a previous study by Yuen et al. (2015) on 12 East Asian cadaveric specimens.…”
Section: Discussionsupporting
confidence: 90%
“…Besides determining the appropriate epiphyseal screw lengths, these figures can also be used to avoid penetration of the posterior cortex while drilling, thus reducing fluoroscopic radiation during surgery and minimizing the risk of intra-operative soft tissue injuries. The measurements of the epiphyseal screws lengths in the entire cohort are in accordance with a previous study by Yuen et al (2015) on 12 East Asian cadaveric specimens. Yuen et al (2015) reported mean Ulnar 1, Ulnar 2, Radial 3 and Radial 4 screw lengths of 20 mm, 20.8 mm, 19.6 mm and 15.4 mm, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…According to the literature, screw penetration greater than 1.0 mm is likely to cause problems (7,16). Therefore, some authors have proposed that distal screws should be routinely 2-4 mm shorter than measured (5,10,23,28,29) and that a screw length of 75 % of the distal radius bone offers fi xation that is as strong as a bicortical construct (30). However, the comminution of the DC usually prevents an adequate drilling through opposite cortex and accurate depth-gauge measurement, and calculating 75 % of an unknown screw measurement is quite tricky.…”
Section: Discussionmentioning
confidence: 99%